ANALISIS KELAYAKAN USAHA RAJANGAN DAUN TALAS BENENG SEBAGAI PENGGANTI TEMBAKAU BERNIKOTIN YANG DITINJAU BERDASARKAN ASPEK NON FINANSIAL (Studi Pada PT Santy Abadi Mandiri) - Desty Anggi Astuti; maulana agung (Jurusan Administrasi Bisnis, FISIP, Universitas Lampung, 2022)
The agricultural sector can be a mainstay in advancing the nation's economy, one of which is through the determination of plant types. Plants that can be the choice of farmers, besides being easy to cultivate, also using affordable costs, are taro beneng (Xanthosoma undipes K. Koch). This plant that is commonly found in Indonesia has emerged with new innovations in its use, namely from its leaves which can be used as a substitute for non-nicotine tobacco. This raises business ideas for novice entrepreneurs, but before starting a business it is necessary to think about overall readiness, one of which is by conducting a business feasibility study, this is done to test and analyze whether the business or business is feasible to run or not based on the aspects that are the feasibility assessment. . This study aims to describe the business feasibility study applied by PT Santy Abadi Mandiri in the business idea of chopping taro beneng leaves as a substitute for nicotine tobacco in terms of non-financial aspects. This study uses a descriptive method with a qualitative approach. Based on the analysis that has been carried out, the results of the study show that: From the legal/legal aspect, environmental aspects, market and marketing aspects, technical and technological aspects, as well as management and human resources aspects, the business of shredding taro beng leaves as a substitute for nicotine tobacco is very effective. worth running.